Happy Puppet syndrome - Sarkar, Priyanka Airen (BMJ Publishing Group, 2011)
Happy Puppet syndrome is characterised by a partial deficit of paired autosomal chromosome 15. It is a neuro-genetic disorder characterised by intellectual and developmental delay, sleep disturbance, seizures, jerky movements (especially hand-flapping), frequent laughter or smiling and usually a happy demeanour. It is also called as Angelman syndrome (AS). People with AS are sometimes known as ‘angels’, both because of the syndrome’s name and because of their youthful, happy appearance. A 6.5-year-old girl is presented and clinical suspicion of AS was raised at the age of 4 years when she presented with mental retardation and epilepsy, absence of speech, inability to gait and unprovoked episodes of laughter. Fluorescent in situ hybridisation chromosomal analysis revealed micro deletion on the maternally derived allele of 15q chromosome.